The prognostic relevance of full-thickness burns on ABSI - Gorenflo, J.; Reichert, Bert; Registry, German Burn; Reif, Simon; Megas, Ioannis Fivos; Billner, Moritz (Burns, 2024)
Introduction The Abbreviated Burn Severity Index (ABSI) by Tobiasen, which is commonly used to estimate the mortality risk of severely burned patients, calculates an additional point for the existence of full-thickness (third-degree) burns. [1] However, the score does not consider the extent of how much of the burnt body surface was affected by thirddegree burns. To understand whether there is a way to improve ABSI prediction power, this study aims to determine the influence of full-thickness burns on survival rates and how it affects the predictive precision of the ABSI. Material and methods In this study, the statistical evaluation of 2538 patients collected prospectively in the context of the German Burn Registry was carried out. A linear regression analysis was carried out to show the prognostic relevance of full-thickness burns. Age, sex, TBSA (Total Body Surface Area), and the presence of an inhalation injury were also observed as further influencing factors. Results Among the 2538 patients meeting our inclusion criteria, full-thickness burns were found in 1233 patients. In patients with a TBSA below 20 %, the extent of full-thickness burns is not relevant to the prognosis in terms of survival probability (p = 0.124). With more than 20 % TBSA, the extent of third-degree burns is of significant relevance (p = 0.000). In patients without full-thickness burns and calculated ABSI values ≥ 12 the survival rate of 46 % was noticeably better than the predicted survival rate of < 10 % according to the ABSI-Score, whereas the predicted survival rate in patients with third-degree burns (< 10 %), closely matched with the observed survival rate of 11 %. Conclusion For patients with a TBSA < 20 %, the presence of full-thickness burns is not relevant for survival. In contrast to this observation, the percentage of full-thickness burns is of crucial prognostic importance for patients with a TBSA of > 20 %. By adjusting the ABSI and taking into account the exact percentage of third-degree burns, an improvement in the prognostic precision of the score could be achieve
Keywords: ABSI; Full-thickness burns; Survival